Pengaruh Harga dan Ulasan Produk Terhadap Keputusan Pembelian Konsumen pada Marketplace Shopee Studi Kasus Masyarakat Kota Jambi - Joselyn Eprilya; Agnes Clarissa; Leonita Leonita; Yossinomita Yossinomita (Prosiding Seminar Nasional Ilmu Teknik, 2025)
This research aims to examine how prices and reviews influence consumers 'purchasing decisions on the Shopee platform in Jambi City. The rapid development of e-commerce has encouraged consumers to be more careful and discerning when selecting products, making price and product reviews important considerations in buying decisions. This study employed a quantitative approach via a survey method for data collection. The questionnaires were distributed online and successfully gathered responses from active Shopee users in Jambi City. Purposive sampling was employed to make sure that respondents met research criteria. The information gathered underwent analysis using IBM SPSS Statistics 27, which involved conducting assessments of validity, reliability, and classical assumptions, and multiple regression tests to see the impact of each variable on buying decisions. The study revealed that product price and reviews hold an important and relevant impact on consumer buying decisions. This research indicates that the more competitive the price and the better the quality, the bigger the possibility of customers buying products on Shopee.